Effect of Ebenatide on glycemic metabolism and body fat in patients with type 2 diabetes mellitus - Xu, Cheng-lan; Kong, Xiao-cen; Liu, Xiao-mei; Xu, Xiao-hua; Liu, Bing-li; Ma, Jian-hua (Frontiers in Endocrinology, 2025)
AimInvestigate effects of Ebenatide, a novel glucagon-like peptide-1 analogue, on glycemic control and body composition in type 2 diabetes mellitus (T2DM).MethodsThis randomized, prospective, interventional study enrolled 78 subjects (76 finished). Subjects were randomized to either the Ebenatide group (52 subjects, Ebenatide for 52 weeks) or the placebo group (24 subjects, placebo for 24 weeks followed by Ebenatide for 28 weeks) according to a 2:1 allocation ratio. Assessments included continuous glucose monitoring and body composition analysis.ResultsThe Ebenatide group showed significantly lower in hemoglobin A1c (HbA1c), mean blood glucose (MBG), time above range (TAR) and standard deviation (SD), along with improvement of time in range (TIR) at Week 24 and Week 52 compared to baseline (P<0.05). The triglyceride-glucose index (TyG) decreased at Week 52 compared with baseline (P<0.01). Compared with the placebo group, the Ebenatide group demonstrated greater reductions in HbA1c and TAR and improved TIR at Week 24 (P<0.05), but no difference at Week 52. Body composition analysis showed that the Ebenatide group had significant declines in weight, BMI, body fat and waist-to-height ratio (WHtR) (P<0.05). Compared with baseline, the Ebenatide group exhibited decreased blood pressure and hemoglobin levels and elevated serum amylase and lipase levels at Week 24 and Week 52 (P<0.05). Adverse events were limited to gastrointestinal reactions.ConclusionEbenatide treatment for 24 weeks significantly improved HbA1c, TIR, TyG, weight and WHtR in T2DM subjects, with these benefits sustained for at least 52 weeks.Clinical trial registrationhttps://clinicaltrials.gov/, identifier NCT05990374.